Controlling the cannibalism of African catfish juvenile by 17β‒estradiol hormone administration and the stocking density determination - Khoirotun Nisa Siregar; Fajar Maulana; Muhammad Zairin Jr.; Alimuddin Alimuddin; Widanarni Widanarni (Jurnal Akuakultur Indonesia)
An effort to increase the production of juvenile catfish is limited by the high mortality rate, especially caused by cannibalism. The hormonal treatment has been conducted as an effort to control cannibalism. This study used completely randomized factorial design, consisted of six treatments and three replications. There were two factors examined in this study, the first factor was different doses of 17β‒estradiol hormone (0, 30, and 60 mg estradiol‒17β/kg) incorporated in the feed, and the second factor was stocking density (150 and 300 fish/m2). Juvenile catfish with the size of 4.0 ± 0.1 cm were reared for 30 days in the 84 L aquarium. The results showed that hormone treatment could reduce cannibalism rate,  type-I and II cannibalism compared to control (P<0.05). The results showed that the lowest of mortality was obtained in the treatment B (17β‒estradiol administration of 30 mg/kg, at stocking density of 150 fish/m2; P<0.05). The lowest cortisol level was found in treatment F, and the highest estradiol level was found in treatment F (17β‒estradiol administration of 60 mg/kg, at stocking density of 300 fish/m2; P<0.05). The lowest of blood glucose level was found in treatment B (P<0.05). The highest specific weight growth was found in the stocking density of 150 fish/m2 (P<0.05). The results of this study indicated that administration of 17β‒estradiol in feed could reduce the level of cannibalism in African catfish juvenile.